2010
DOI: 10.1007/s10753-010-9199-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Inflammation Induced by Zymosan Results in Activation of Intrarenal Renin-Angiotensin System in Adult Offspring Rats

Abstract: Prenatal exposure to inflammation produces offspring that are hypertensive in adulthood. The present study was to explore the role of intrarenal renin-angiotensin (Ang) system in the development of hypertension programmed by prenatal exposure to zymosan. Pregnant rats were randomly divided into control group and zymosan group (n = 6). Rats in these two groups were administered intraperitoneally with 0.5 ml vehicle and 2.37 mg/kg zymosan, respectively, on the eighth, tenth, and 12th day during gestation. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Environmental factors and genetic factors are two important factors for the development of hypertension, but it has also been assured that the later development of hypertension can be programmed by an adverse fetal environment3418192021. Prenatal inflammation as a common event during pregnancy has been proven to be strongly associated with the hypertension in adult offspring5678. Our group previously found that prenatal exposure to systemic inflammation induced by LPS stimulation led to hypertension, increased body weight, alteration of the intrarenal RAS, and renal damage in adult offspring rats910.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors and genetic factors are two important factors for the development of hypertension, but it has also been assured that the later development of hypertension can be programmed by an adverse fetal environment3418192021. Prenatal inflammation as a common event during pregnancy has been proven to be strongly associated with the hypertension in adult offspring5678. Our group previously found that prenatal exposure to systemic inflammation induced by LPS stimulation led to hypertension, increased body weight, alteration of the intrarenal RAS, and renal damage in adult offspring rats910.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal inflammation exposure is one of the most common events in pregnant women who suffer from some inflammatory diseases. Several previous studies indicate that prenatal inflammation exposure is highly associated with adult hypertension in the offspring5678. Lipopolysaccharide (LPS) is a toxic component of cell walls of gram-negative bacteria, often used as a nonspecific immuno-inflammatory stimulant to mimic the bacterial inflammatory response9.…”
mentioning
confidence: 99%
“…RNA was analyzed by real-time PCR as described previously [11]. The PCR primers used were designed by Premier 5.0 (PREMIER Biosoft International, Palo Alto, CA, USA) based on published nucleotide sequences for rat Cx37 (forward: 5′- CAT CCG ATA CTG GGT GCT GC -3′; reverse: 5′-CGC CGA GAC AGG TAA ATG ACG-3′), rat Cx43 (forward: 5′-GAC ATG GGT GAC TGG AGT G-3′; reverse: 5′-TTG AGT GTT ACA GCG AAA GG-3′), rat Cx40 (forward: 5′-GAA AGA GGT GAA CGG GAA GA-3′; reverse: 5′-GCC ACA GCC ATC ATA AAG ACA-3), rat Cx45 (forward: 5′- GAG ATG GAG TTA GAA AGC GAG AA-3′; reverse: 5′- CAG GAA ATA CTG CCC TAT GAG A-3) and rat β-actin (forward: 5′- ACG GTC AGG TCA TCA CTA TCG-3′; reverse: 5′- GGC ATA GAG GTC TTT ACG GAT G-3).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the offspring showed significantly increased body weight and abdominal fat weight [8], [9]. Furthermore, alterations in the local renin-angiotensin system and renal damage resulting from prenatal LPS or Zymosan exposure were interpreted to the elevated blood pressure in adult offspring rats [10], [11]. However, the mechanisms behind relationship still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The 6-week-old offspring of these rats displayed significantly higher blood pressure levels compared with the respective controls, and at 24 weeks, a hyper-tension level of 140 mmHg was observed. Furthermore, the body weights of offspring in the experimental group were significantly increased compared with that of the controls (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 86%